A Medieval Way to Modernity: Wilhelm R. Valentiner, Late Medieval Sculpture and German Expressionism. (2nd April 2016) - Mascolo, Marco M.
Abstract : This article traces how Wilhelm Reinhold Valentiner (1880–1958) studied, approached and criticised late medieval Italian sculpture and German Expressionism, from the turn of the twentieth century until the eve of World War II. It explores Valentiner's theoretical positions through a thorough analysis of his writings and biography, from his time as curator at the Metropolitan Museum of Art (1908–1914), through his World War I years in Germany (1914–1923), and, finally, to his second period in the United States (1923–1935). For Valentiner, late medieval Italian sculpture and German Expressionism were linked by similar and comparable formal qualities. In his writings Valentiner created a bidirectional dialogue between past and present. He interpreted the stylistic characteristics of late medieval sculpture by referring to Expressionist formal simplifications; but he also elevated Expressionism as a pure modern form of art, by creating a "tradition" for it, and interpreting it as the final step of an artistic lineage that had begun in the late Middle Ages.